Healthy worker effect in cohort studies on chronic bronchitis - Radon, Katja; Goldberg, Marcel; Becklake, Margaret (Scandinavian Journal of Work, Environment & Health, 2002)
' ' OBJECTIVES ': 'Despite the recognition of selection biases arising from the healthy worker effect in occupational mortality studies, the possibility of similar effects in occupational cohort studies on respiratory symptoms is not well known. Two mechanisms are responsible for the healthy worker effect in respiratory cohort studies. One is health-based selection of workers into employment (healthy hire effect), and the other is health-based differential losses to follow-up (healthy worker survivor effect). The aim of the present paper was to estimate the magnitude of the healthy worker survivor effect in cohort studies of symptoms of chronic bronchitis. ' ' METHODS ': 'A meta-analysis of occupational cohort studies of symptoms of chronic bronchitis was performed that included published articles identified in searches of the Medline bibliographic databases between 1980 and March 2001 and the reference lists of the located articles. ' ' RESULTS ': 'Eight cohort studies were identified using an a priori selection criterion. The pooled odds ratio of the prevalence of chronic bronchitis for subjects leaving the cohorts was 1.23 when these subjects were compared with those who remained under study (95% confidence interval 1.04-1.44). ' ' CONCLUSIONS ': 'The prevalence of respiratory symptoms among exposed workers may be underestimated if the healthy worker survivor effect is not taken into account.
Keywords: chronic bronchitis; cohort study; epidemiology; healthy worker effect; occupational medicine; selection bias